Kobiety świata polityki na okładkach wybranych polskich tygodników w latach 2014–2015 - Brzoza, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The image of women representing the world of politics, seen on the covers of selected Polish weekly magazines in the years 2014–2015, is the area of interest in this article. The conducted analysis helped to determine the dominance of occurrence and the way of portraying human beings, with special attention paid to the female gender, on the covers of 9 magazines („Do Rzeczy”, „Gazeta Polska”, „W Sieci”, „Polityka”, „Wprost”, „Newsweek Polska”, „Przegląd”, „Tygodnik Powszechny”, „Gość Niedzielny”). An essential part of these deliberations was focused on women involved in political life. The method of presenting female politicians was identified, and the names of those most frequently appearing on the covers of analyzed weekly magazines were indicated. Further endeavor was made to grasp the role of the female gender in modern politics, by using the method of imaging, visible on the covers of chosen weekly magazines.
Women representing the world of politics on the covers of selected polish weekly magazines in the years 2014–2015
Keywords: politics; woman; cover; weekly; gender